2016
DOI: 10.1108/dat-03-2016-0010
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing alcohol screening and brief intervention among people receiving opioid agonist treatment: qualitative study in primary care

Abstract: Purpose Problem alcohol use (PAU) is common and associated with considerable adverse outcomes among patients receiving opioid agonist treatment (OAT). The purpose of this paper is to describe a qualitative feasibility assessment of a primary care-based complex intervention to promote screening and brief intervention for PAU, which also aims to examine acceptability and potential effectiveness. Design/methodology/approach Semi-structured interviews were conducted with 14 patients and eight general practitione… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Semistructured interviews will be conducted with 16 health care professionals working in mental health services (n=16) to inform the complex intervention . Although it is difficult to predict the number of participants required to reach data saturation, our previous qualitative work [72,73] has indicated that 12 to 16 verbatim are required.…”
Section: Methodsmentioning
confidence: 99%
“…Semistructured interviews will be conducted with 16 health care professionals working in mental health services (n=16) to inform the complex intervention . Although it is difficult to predict the number of participants required to reach data saturation, our previous qualitative work [72,73] has indicated that 12 to 16 verbatim are required.…”
Section: Methodsmentioning
confidence: 99%
“…Semistructured interviews will be conducted by a member of the research team with health care professionals (n=12) and patients (n=12; or until analytical saturation is reached) at follow-up, purposively sampled from recruited practices and patients. Interviews will be guided by an interview schedule informed by our previous feasibility study in Irish primary care [ 33 ], including participants’ lived experiences of HCV including barriers and facilitators to treatment, as well as questions exploring participants’ experiences and acceptability of the study intervention. With purposive sampling, the researcher samples particular settings, persons, or events deliberately selected for the important information they can provide that cannot be acquired as well from other choices [ 34 ].…”
Section: Methodsmentioning
confidence: 99%